KONSELING KELOMPOK SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN MENGUNGKAPKAN GAGASAN PADA SISWA KELAS VIII ASEMESTER I SMP NEGERI 1 DENPASAR TAHUN PELAJARAN 2016/2017 - Erawan, Gede (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2019)
The background of this study is the existence of a problem, namely the low ability to express ideas to students of class VIII A Semester I of SMP Negeri 1 Denpasar, so that these conditions can hinder the teaching and learning process in general. By knowing there are problems, the researchers want to overcome by carrying out research through group counseling, the purpose of this study is through group counseling can improve the ability to express ideas. This research was carried out in a cycle system, the results of the actions were monitored by observation and questionnaire. The results of monitoring are deformed descriptively. The evaluation results show that group counseling can improve the ability to express ideas. Based on the initial data is 52.50% to 75.00% after the first cycle was carried out, in the second cycle after the treatment improvement from the deficiencies found in the previous cycle increased to 97.50%. in this second cycle has fulfilled the determined success indicators and the cycle was declared not continued, the conclusion of this study that group counseling can improve the ability to express ideas to students of class VIII A Semester I Denpasar 1 Public Middle School 2016/2017 Academic Year